Financing American Enterprise-The Story of Commercial Banking. - McKinley, Erskine; Trescott, Paul B. (Journal of Finance, 1963)
This work is a general history of banking in America, emphasizing the relation between bank credit and the development of the American economy. The effects on the banking industry of population growth, industrialization, technological advance, and changes in the forms and sizes of business firms are examined.